Implementation of Social Studies Learning at Cimahi City Junior High School Post-Covid-19 Pandemic - ARNIE FAJAR (Universitas Negeri Semarang, 2024)
This study aims to determine the implementation of social science learning at the end of the COVID-19 pandemic in junior high schools in Cimahi City. The approach used is qualitative with a descriptive method. The research instruments used are observation, interviews, documentation, and literature studies. Data analysis is carried out interactively simultaneosly as data collection and continous until data collection is complete. Furthermore, data reduction is carried out, data exposure is done, and finally, conclusions are made. The results showed that junior high school social studies teachers in Cimahi City had implemented social studies learning at the end of the COVID-19 pandemic by planning, implementing, and conducting learning assessments following applicable laws and regulations. Learning planning includes preparing annual programs, semesters, syllabi, and lesson implementation plans, although some social studies teachers must complete them. Most social studies teachers have carried out learning, including preparatory or preliminary activities, core learning, and closing, following the learning syntax very well, and some are included in the excellent category and quite well according to applicable regulations. However, the enrichment program has not been able to be implemented optimally. Social studies teachers have also conducted learning assessments following aplicable laws and regulations, including affective, cognitive, and psychomotor domain assessments.